The Journey toward Voluntary Public Health Accreditation Readiness in Local Health Departments: Leadership and Followership Theories in Action - Carman, Angela L. (Frontiers in Public Health, 2015)
Local health department directors’ intent on getting their organizations ready for accreditation must embrace the blurring of leader/follower lines and create an accreditation readiness team fueled not by traditional leader or follower roles but by teamship.